Genetic variation in APE1 gene promoter is associated with noise-induced hearing loss in a Chinese population - Shen, Huanxi; Dou, Jianrui; Han, Lei; Bai, Ying; Li, Qian; Hong, Zhiqiang; Shi, Jian; Zhang, Hengdong; Zhang, Feng; Du, Cheng; Tong, Zhimin; Zhu, Baoli (International archives of occupational and environmental health, 2016)
Objective To investigate whether the apurinic/apyrimidinic endonuclease 1 ( APE1 ) 1349 T>G and -656 T>G polymorphisms were associated with the risk of noise-induced hearing loss (NIHL) in a Chinese population. Methods The two APE1 polymorphisms were analyzed among 613 NIHL workers and 613 normal hearing workers using the minor groove binder TaqMan probe assay. Results We found that the APE1 -656 TT genotype was associated with a increased risk of NIHL [adjusted odds ratio (OR) 1.46, 95 % confidence interval (CI) 1.05–2.06]. This increased risk was more pronounced in the stratification analysis. Furthermore, we found that subjects with two risk genotypes ( hOGG1 Cys/Cys, APE1 -656 TT) had a significantly increased risk of NIHL (adjusted OR 1.91, 95 % CI 1.27–2.88). Conclusion Our study identified that the APE1 -656 T>G polymorphism may contribute to the susceptibility of NIHL.